Effect of inter-observer variation on the association between contamination hazards and the microbiological quality of water sources: A longitudinal study - Okotto-Okotto, J.; Silva, D.T.G. da; Kwoba, Emmah; Thumbi, Samuel M.; Wanza, P.; Yu, W.; Wright, J.A. (MDPI, 2020)
Sanitary risk inspection protocols are often used to identify contamination hazards at water sources; however, different observers sometimes struggle to record hazards consistently. This study aimed to assess the effect of inter-observer variation in hazard observations on the strength of relationships between observed hazards and the bacterial contamination of water sources, particularly relationships with animal-related hazards. In a longitudinal study, five surveyors independently recorded hazards at 93 water sources used by 234 households in Siaya County, Kenya, in both wet and dry seasons. One surveyor collected samples from sources for subsequent Escherichia coli and intestinal enterococci testing. The relationship between each surveyor's hazard observations and high bacterial contamination was examined using logistic regression. After controlling for water source type and preceding rainfall; percentage scores for animal-related hazards were significantly related to high contamination with enterococci and E. coli for one surveyor (odds ratio 1.02; 95% confidence intervals 1.00-1.03 for both parameters), but not for the remaining four surveyors. The relationship between observed contamination hazards and the microbiological contamination of water sources is sensitive to variation in hazard recording between surveyors. Sanitary risk protocols should be designed to enable robust and consistent observation of hazards.